2012
DOI: 10.1016/j.mce.2012.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fibroblast growth factor-8b target genes associated with early and late cell cycle events in breast cancer cells

Abstract: (2012). Identification of fibroblast growth factor-8b target genes associated with early and late cell cycle events in breast cancer cells. Molecular and Cellular Endocrinology, 358(1), 104-115. DOI: 10.1016/j.mce.2012.03.009 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Transcriptional activation of the FGFR1 gene by E2F binding to its promoter has been shown [21]. Interestingly, a gene set enrichment analysis (GSEA) of FGF-8-controlled genes in microarray studies showed that the E2F binding motifs were highly enriched among the FGF-8 upregulated genes [22]. In fibroblasts, cyclin D1 overexpression leading to activation of the Sp1 [23] and the Rb/E2F pathways has been shown to be associated with increased FGFR1 transcription [24].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional activation of the FGFR1 gene by E2F binding to its promoter has been shown [21]. Interestingly, a gene set enrichment analysis (GSEA) of FGF-8-controlled genes in microarray studies showed that the E2F binding motifs were highly enriched among the FGF-8 upregulated genes [22]. In fibroblasts, cyclin D1 overexpression leading to activation of the Sp1 [23] and the Rb/E2F pathways has been shown to be associated with increased FGFR1 transcription [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies of ER + breast cancer cells demonstrated that FGF9 can cooperate with estrogen to induce expression of the transcription factor TBX3, leading to expansion of the cancer stem cell population [37]. In other studies, microarray analysis was performed on ER − breast cancer cells treated with FGF8b to identify novel genes involved in mediating FGF-driven tumorigenesis [62]. Results from these studies demonstrated that FGF8b regulates the expression levels of a number of genes involved in proliferation and survival, including BTG2, CCND1, CCNB1 (cyclin B), PLK1 , survivin and aurora kinase A [62].…”
Section: Overview Of Fgf/fgfr In Breast Cancermentioning
confidence: 99%
“…In other studies, microarray analysis was performed on ER − breast cancer cells treated with FGF8b to identify novel genes involved in mediating FGF-driven tumorigenesis [62]. Results from these studies demonstrated that FGF8b regulates the expression levels of a number of genes involved in proliferation and survival, including BTG2, CCND1, CCNB1 (cyclin B), PLK1 , survivin and aurora kinase A [62]. Using gene profiling approaches, it has also been shown that FGFR1 activation leads to increased expression of epidermal growth factor (EGF) family members, which then act on the tumor cells via ErbB family member activation to promote proliferation and migration, demonstrating a functional link between FGFR and ErbB activity in tumor cells [63,64].…”
Section: Overview Of Fgf/fgfr In Breast Cancermentioning
confidence: 99%
“…Furthermore, we confirm by qPCR, FGFR3-TAK1-mediated downregulation of TNFAIP3, a known NFκB target gene identified in our microarray analysis (Table 2; [63]). Other TAK1-regulated NFκB target genes identified by our microarray that have also been implicated in FGF signaling include BCL2L11, TNFAIP2, CCND1, CCL20 (MIP-3α), and BCL2L1 (Bcl-xL), the latter two shown to be regulated by FGF signaling in an NFκB-dependent manner [64][66]. The ability of FGFR3-TAK1 signaling to activate NFκB is interesting given that we map FGFR3 interaction with TAK1 to the same region (amino acids 441–579 of the C-terminal tail; Figure 1) as the TAB2/3 regulatory proteins (amino acids 479–547) required for TAK1 activation by Ser/Thr phosphorylation [50].…”
Section: Discussionmentioning
confidence: 99%